Strategi Meningkaatkan Partisipasi Masyarakat Dalam Pembangunan Wisata Pantai Biru Di Kelurahan Tanjung Merdeka - Cantika Batary Prisilla, Dwi; Aksa, Kamran; Idris Taking, Muhammad (Journal of Urban Planning Studies, 2024)
Dwi Cantika Batary Priscilla, 2023 "Strategy to Increase Community Participation in the Development of Blue Beach Tourism". Supervised by Kamran Aksa and Idris Taking. The city of Makassar has various tourism potentials, including one of the tourist attractions on the Blue Beach. Blue Beach is located in Tanjung Merdeka Village, Tamalate District, Makassar City, South Sulawesi. Communities in Blue Beach tourism have been given the opportunity as well as the trust to manage the Blue Beach tourist attraction with the capabilities of each group or individual related to tourism. Even though the opportunities provided are very broad, the community still lacks the will and ability to develop related activities. The purpose of this study was to determine what factors influence community participation in the development of blue beach tourism and also to determine the form of community participation strategies in the development of blue beach tourism in Tanjung Merdeka Village, Makassar City. The research method used to determine the factors that influence community participation in the development of blue beach tourism is using chi-square analysis While the method used to determine the form of community participation strategy in the development of blue beach tourism is SWOT analysis (Strangths, Weaknesses, Opportunities, and Threats). Based on the results of the analysis carried out, it is known that the factors that have a strong influence on community participation in the development of blue beach tourism are the factors of the opportunities provided by the community and the willingness of the community to participate. The form of the strategy set out in this paper is to use the SO strategy or take advantage of the strengths you have to optimize the opportunities that exist. Keywords: Community participation, Chi-Square, SWOT